Three new showy but endangered Cyrtochilum species (Oncidiinae: Orchidaceae) from Peru - Dalström, Stig (Universidad de Costa Rica, 2013)
Three new Cyrtochilum species from Peru that are endangered by habitat destruction, are here described, illustrated and compared with similar species.